Wpływ technologii informatycznej na działalność małych i średnich przedsiębiorstw regionu Podkarpacia - Kud, Krzysztof (Computer Support of Innovation in Small Business Enterprises of Podkarpacie, 2006)
The research concerning IT support of business activities in the SME sector was conducted in 2005 on the area of Podkarpackie voivodship. The majority of surveyed companies own 1-9 computers and use Microsoft software. The straight majority of enterprises use Internet, but in the group of micro-enterprises fact of possesing own WWW site is underestimated. Great educational needs exist especially in the range of DBMS subject.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 492-498